From Alexandria to Babylon : Near Eastern languages and Hellenistic erudition in the Oxyrhynchus glossary (P. Oxy. 1802 + 4812) - Schironi, Francesca (Sozomena., 2009)
This book provides the first full edition and commentary of the Oxyrhynchus Glossary (POxy 1802 and 4812). This is a unique document both for the history of Greek lexicography and for the study of the cultural and linguistic exchange between the Greeks and the "others" in the Hellenistic near East. The fragment contains a fully alphabetized glossary with lemmas defined as "Persian", "Babylonian" and "Chaldaean", as well as lemmas taken from Greek dialects or common Greek. The entries are rich in quotations from ancient authorities including Berossus, Apollodorus and Erasistratus. This glossary.